Transition and adaptation to higher education and the quest for success in Portuguese institutions - Soares, Andreia Martins (2016)
Despite the many important changes occurred in Portuguese higher education institutions since the last years of Estado Novo (New State) and the efforts to accomplish the demanding mission of preparing students for the challenges of the Europe of Knowledge, severalindicators put the Portuguese higher education far from an educational system that is intended to be inclusive, differentiated and of high quality. The national research focused (1) on the understanding of academic success and of transition and adjustment to the higher education process and (2) on subsequent planning / implementation of actions to promote them has been a good contribution to the prosecution of previously mentioned pretensions. This review article will address these complex phenomena, emphasizing the latest research perspectives and results, as well as the answers that national postsecondary institutions have developed to promote academic success (which, in its broader meaning, includes a successful transition and adaptation process).